Evidence of Declining Dietary Diversity Among Children Aged 1–5 Years Between 2005 and 2017 in Lower-Income Countries. (29th May 2020) - Salmon, Kyle; Shin, Dayeon; Kmush, Brittany; Wallia, Bhavneet; Bellows, Anne; Larsen, David
Abstract: Objectives: We sought to estimate trends in dietary diversity in children aged 1–5 years living in lower-income countries. We hypothesized that dietary diversity is increasing over time in this population, independent of changes in wealth. Methods: We utilized 89 Demographic and Health Surveys conducted in 59 countries to cross-sectionally measure two separate outcomes, 1) the number of different types of food the child ate in the previous 24 hours (dietary diversity) and 2) the proportion of children who only ate one type of food in the previous 24 hours. We then estimated change over time across the years 2005–2017 in both a child-level analysis using negative binomial regression and logistic regression models, respectively. We also conducted a country-level analysis using a meta-analysis approach. In the child-level analysis, we tested for two separate interactions, one of year and wealth to determine if dietary diversity is changing differently depending on wealth, and one of year and place of residence (urban/rural) to determine if dietary diversity is changing differently depending on the place of residence. Results: Across 59 lower-income countries, these data suggest an overall trend of decreasing dietary diversity over time, and an increase in the proportion of children who only consumed one food type in the previous 24 hours. We observed an annual decline in dietary diversity of 4% (95% confidence interval = 3.7–5.2%) among children 1–5 years of age from 2005–2017. No significant differences relative to wealth or place of residence were observed in the decline. We also observed an annual increase in the odds of a child only eating one type of food in the previous 24 hours of 5.8% (95% confidence interval = -0.5 – 12.5%) from 2005–2017. Conclusions: These results suggest an unexpected decline in dietary diversity in lower income countries. The decline in dietary diversity could have significant implications for inadequate micronutrient intake of children. Although diets are thought to improve as the world's wealth increases, diet quality appears to be declining in lower income countries in some cases, concurrent with increases in wealth over this same time period. Funding Sources: This research was funded through Syracuse University's Office of Undergraduate Research and Creative Engagement (SOURCE).